Hubungan Tingkat Pengetahuan Dengan Kepatuhan Pengobatan Pada Remaja Penderita Hipertensi - Cyntia Nur Anggraeni; Rosly Zunaedi; Ika Arum Dewi Satiti (Media Husada Journal Of Nursing Science, 2026)
Abstract Hypertension in adolescents is an emerging public health problem that requires long-term management. Medication adherence plays an important role in controlling blood pressure and preventing complications; however, adherence among adolescents remains suboptimal. Previous studies have primarily focused on adults, while research examining the relationship between knowledge level and medication adherence among adolescents with hypertension is still limited. Therefore, this study focused on adolescents as its research novelty. This study aimed to analyze the relationship between knowledge level and medication adherence among adolescents with hypertension at Kedungkandang Public Health Center. This quantitative analytic study employed a cross-sectional design. A total of 30 respondents were selected using the total sampling technique. Knowledge level was measured using a hypertension knowledge questionnaire, while medication adherence was assessed using the Morisky Medication Adherence Scale (MMAS-8). Data were analyzed using Somers' d test with a significance level of 0.05. The results showed that 50% of respondents had a moderate level of knowledge, and 50% had moderate medication adherence. Statistical analysis revealed a significant relationship between knowledge level and medication adherence (p = 0.029) with a Somers' d coefficient of 0.617, indicating a strong positive relationship. These findings suggest that higher knowledge levels are associated with better medication adherence among adolescents with hypertension. This study highlights the importance of continuous health education to improve medication adherence and reduce the risk of hypertension-related complications among adolescents.